Alternative Theatre in Britain in the Late 70s and in the 80s - Moya Jones (Revue Française de Civilisation Britannique)
In the 1960s and 1970s in Britain there was a growing number of small theatre groups with many different origins and affiliations and were all gathered under one heading as "underground theatre" by the London listings magazine Time Out, though they called themselves by other titles such as fringe /alternative /experimental or community theatre. These groups and their cultural production were in some way opposed to the dominant social and cultural values of the mainstream. " The election of a neo-liberal government in 1979, promoting monetarism and market forces, caused increasing economic pressure on these groups which were almost all struggling financially. This article examines what made these theatre companies different, not just in terms of content but also in the economies of these groups. What were their incomes and expenditures?. How did they survive? The paper addresses several of the key questions raised in the call for papers, the most crucial concerning the relation between those who were opposed to the mainstream but depended on mainstream institutions for the means to survive. The information is drawn mainly from an unpublished thesis.